Report on the Meetings of the Administrative Committee of the Inter-american Institute of Agricultura Sciences - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2021)
212 páginas.